Adsorption kinetics and thermodynamics studies of copper (II) and zinc (II) on hydroxyapatite pellets - Alon, Candice A. (College of Engineering, University of the Philippines Diliman, 2015)
Heavy metals in wastewater and water sources can cause several harmful effects to animals, plants and human beings. Many studies had been made on the application of hydroxyapatite (Hap) on wastewater treatment. However, most studies utilized powder or nanoparticles which may raise disadvantages on water treatment processes as subsequent filtration is needed to remove reacted residues. In this study, the adsorption of Cu2+ and Zn2+ ions on hydroxyapatite surfaces was investigated by batch kinetics and thermodynamics studies. Hydroxyapatite adsorbents were extracted from porcine skull and were pelletized through mechanical pressing and sintering. The batch method were performed using 10 ppm metal concentration in aqueous solutions with adsorption time ranging from 5 to 90 minutes and temperature ranging from 25ºC to 35ºC. The fabricated Hap pellets were then observed to have rough surface with 15.87% surface porosity as seen in 5000x SEM images. Batch adsorption test was performed for a maximum of ninety minutes resulting to 96.24% copper removal and 42.49% zinc removal. This entails that hydroxyapatite has 0.79 mg/g and 0.18 mg/g adsorption capacity for copper and zinc ions, respectively. The adsorption process for copper and zinc was also determined to best fit both the pseudo-first-order and liquid film diffusion kinetic models. Adsorption of copper and zinc in HAp pellets at varying temperatures was analyzed and resulting thermodynamic parameters indicated that copper adsorption was a spontaneous process while zinc adsorption was nonspontaneous. It was also observed that the highest percent of copper removal occurs at 30ºC and at 25ºC for zi